Concomitant pulmonary vein isolation and percutaneous closure of atrial septal defects: A pilot project. (6th November 2019) - Evertz, Reinder; Houck, Charlotte A.; ten Cate, Tim; Duijnhouwer, Anthonie L.; Beukema, Rypko; Westra, Sjoerd; Vernooy, Kevin; de Groot, Natasja M. S.
Abstract: Background: Patients with an atrial septal defect (ASD) are at increased risk of developing atrial fibrillation (AF). Currently percutaneous ASD closure is the preferred therapeutic strategy and although pulmonary vein isolation (PVI) for AF is feasible after ASD closure, the transseptal puncture can be technically challenging and probably increases the perioperative risk. A staged approach, with PVI several months before ASD closure, has been recommended for patients already scheduled for closure, but no data are available on combined procedures. Purpose: This pilot study evaluates the feasibility of a combined procedure of PVI and ASD closure in patients with a hemodynamic important ASD and documented AF. Methods: In one procedure, PVI was performed prior to placement of the ASD closure device. Transseptal access for PVI was obtained via wire passage through the ASD in all patients. Patients were followed with 5‐day‐holter monitoring at 3, 6, and 12 months. Recurrence of AF was defined as a documented, symptomatic episode of AF. Results: The study population consisted of five patients (four females, mean age: 58 (±3) years). Acute PVI was achieved in all patients. Only one patient had a small residual ASD after closure. Besides a small groin hematoma in two patients, no complications occurred. After 12‐month follow‐up, three patients were free of AF recurrence (60%). Conclusion: This study shows that a combined PVI with ASD closure is feasible with an acceptable success rate of AF free survival. These preliminary results in a small patient group warrants a larger trial.